FEATURES OF DEVELOPMENT OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCIES OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - O.Yu. Nesterova (Academy of Cognitive and Natural Sciences, 2008)
The article deals with the research of communicative competence development peculiarities of the students of higher educational establishments. The paper describes 6 stages of training activity of the students based on the support materials as a means of educational and pedagogic purposes of training practice reaching.